EFFECT OF AUDIT COMMITTEE INDEPENDENCE ON ENVIRONMENTAL SUSTAINABILITY DISCLOSURE (Journal of Global Accounting, 2024)
This study evaluated the effect of audit committee independence on environmental sustainability disclosure of listed oil and gas firms in Nigeria covering a period scope of twelve (12) years from 2012-2023. This study specifically assessed the effect of audit committee independence on effluent disclosure using panel data from the annual reports and accounts of nine (9) listed oil and gas companies in Nigeria. Ex-Post Facto research design was employed while inferential statistics via Pearson correlation coefficient and Panel least square regression analysis was employed to test the hypotheses of the study. The results from the test of hypothesis showed that audit committee independence has significant positive effect on effluent disclosure. This study concludes that audit committee independence has significant effect on environmental sustainability disclosure. Consequently, it is recommended that Audit committee be granted independence to enable them perform their functions effectively.
Keywords: Audit Committee Independence; Effluent Disclosure; Environmental Sustainability; Oil and Gas Firms